Development of batik wastewater treatment for cottage industry / Ku Halim Ku Hamid and Non Daina Masdar - Ku Hamid, Ku Halim; Masdar, Non Daina (2002)
Batik industries produce a variety of waste liquors from the cleaning, processing and dyeing of the fabric. Disposal of batik wastewater of pH ranges 4 to 13 could cause an environmental problem due to the high content of dissolved solid and toxic compound as well as the color body. Standard wastewater treatment analysis was applied to characterize the wastewater. A bench scale of treatment was established using a new coagulant known as KN1. KN1 is a plant based coagulant and most suitable pH for the coagulation process ranging from 5 to 5.9. The results obtained shows that batik wastewater could be treated using this method, followed by removal of color and an inorganic matter using activated carbon. A pilot plant will be designed based on the bench study with stringent requirements such as simple, low cost and users friendly for small batik industries.